2007
DOI: 10.1007/s00428-007-0422-7
|View full text |Cite
|
Sign up to set email alerts
|

CD30 and Epstein–Barr virus RNA expression in sclerosing angiomatoid nodular transformation of spleen

Abstract: Sclerosing angiomatoid nodular transformation (SANT) is a splenic lesion composed of angiomatoid/vascular nodules surrounded by hyalinized/sclerotic stroma, fibroblasts, myofibroblasts, and inflammatory cells. The endothelium within the nodules has a phenotype resembling splenic sinusoids, capillaries, and small veins. Martel et al. (Am J Surg Pathol 28:1268-1279, 2004) suggested that SANT may represent the final pathway of a variety of splenic lesions including inflammatory pseudotumors (IPTs). Epstein-Barr v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 21 publications
4
49
0
1
Order By: Relevance
“…Immunohistochemistry revealed that the proliferating spindle cells were strongly positive for vimentin and α-SMA, but not for CD21, CD31, CD34, or CD68. These results revealed that the internodular lesions of SANT histologically resembled IPT, as described in the previous reports [14,19]. In addition, we determined that the myofibroblasts in the IPT-like area of SANT had a subpopulation of EBV-infected myofibroblasts in one of nine cases.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Immunohistochemistry revealed that the proliferating spindle cells were strongly positive for vimentin and α-SMA, but not for CD21, CD31, CD34, or CD68. These results revealed that the internodular lesions of SANT histologically resembled IPT, as described in the previous reports [14,19]. In addition, we determined that the myofibroblasts in the IPT-like area of SANT had a subpopulation of EBV-infected myofibroblasts in one of nine cases.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, we determined that the myofibroblasts in the IPT-like area of SANT had a subpopulation of EBV-infected myofibroblasts in one of nine cases. Weinreb et al [19] first investigated EBV in SANT, and detected EBV RNA in one of six cases that had diffuse areas resembling IPT, and noted that SANT might be associated with EBV infection. However, there was no data regarding the immunophenotype of the EBER-positive spindle cells in SANT in their description.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations